2021
DOI: 10.1155/2021/5554002
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties and Fatty Acid Profile of Cretan Extra Virgin Bioolive Oils: A Pilot Study

Abstract: Olive oil is considered a valuable ingredient of human diet. It is a good source of mono- and polyunsaturated fatty acids, as well as other bioactive compounds, especially polyphenols. The composition of olive oil depends mainly on the variety of plant, cultivation practices, and manufacturing conditions. Traditional processing methods may ensure better quality and health benefits. Therefore, the aim of the study was the evaluation of antioxidant properties and fatty acid profile of Cretan extra virgin biooliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
1
3
0
1
Order By: Relevance
“…These samples had also significantly similar TPC values (1.85 and 1.80 mg GAE/g, respectively). Our findings are in agreement with those of Nowak et al [21] where a positive correlation between the antioxidant activity (determined by ABTS •+ assay) and the concentration of total polyphenols was observed. Also, in relation to sensorial characteristics, the analysis of variance found that no significant differences for "bitter" and "pungent" were found for samples A and D (Table 2).…”
Section: Total Antioxidant Capacity Determinationsupporting
confidence: 94%
See 2 more Smart Citations
“…These samples had also significantly similar TPC values (1.85 and 1.80 mg GAE/g, respectively). Our findings are in agreement with those of Nowak et al [21] where a positive correlation between the antioxidant activity (determined by ABTS •+ assay) and the concentration of total polyphenols was observed. Also, in relation to sensorial characteristics, the analysis of variance found that no significant differences for "bitter" and "pungent" were found for samples A and D (Table 2).…”
Section: Total Antioxidant Capacity Determinationsupporting
confidence: 94%
“…The total run time was approximately 50 min. The identification of the peaks was performed by comparing the corresponding retention times to those of several standards and quantified as a percentage of the total fatty acids [21].…”
Section: Fatty Acid Profilementioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, food consumption patterns have changed during the last 50 years in most regions, including Crete [31], with adaptation to Westernized dietary patterns, leading to a poor MedDi quality index [32][33][34]. The cardinal feature of a Mediterranean-type diet, olive oil, however, still serves as the principal source of dietary fat in Crete, as in many Mediterranean regions, providing the precious monounsaturated fatty acids (MUFAs) and polyphenols [35,36].…”
Section: Obstacles To the Validation Of Associationsmentioning
confidence: 99%
“…Parâmetros químicos também foram analisados em azeites de oliva virgem grego, em que os achados demonstraram características especiais de amostras de quatro cultivares e sua diferenciação botânica bem sucedida com base na composição de ácidos graxos (Revelou et al, 2021). Em Creta foram avaliadas propriedades antioxidantes e do perfil de ácidos graxos bioativos de azeites extra virgem em comparação com os espanhóis, italianos e gregos comerciais, onde perceberam que a amostra 1 de Creta tinha capacidade antioxidante cerca de 15% maior e teor de polifenol total cerca de 60% maior do que os azeites de oliva extra virgem espanhóis, italianos e gregos, demonstrando também composição favorável de ácidos graxos, principalmente linoléico e αlinolênico, já a amostra 2 de Creta não diferiu significativamente de gregas comerciais (Nowak, et al, 2021).…”
Section: Journal Of Theunclassified